The old revolutionary soldier - Alden, Joseph, 1807-1885 (Preservation and Access for American and British Children's Literature, 1850-1869 (NEH PA-23536-00), 1851)
A boy's kindness to a poor elderly man leads to friendship and stories of the man's experiences in the American revolution.